Quantum chemistry and spectroscopy - Engel, Thomas (Pearson/Benjamin Cummings, 2006)
"Quantum Chemistry and Spestroscopy" focuses on the central ideals and concepts that frame quantum chemistry and spectroscopy. The Author covers key concepts thoroughlt, giving you the solid foundation you need to succeed. Application woven thorought each chapter demonstrate how chemical theories are used to solve real-world chemical problems in biology, environmental science, and material science. Extensive coverage of modern research and new developments in the field show how quantum chemistry is modern, vital, and envolving.